2013
DOI: 10.1002/14651858.cd000504.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Early trophic feeding versus enteral fasting for very preterm or very low birth weight infants

Abstract: Early trophic feeding versus enteral fasting for very preterm or very low birth weight infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 45 publications
0
92
2
5
Order By: Relevance
“…21 HM is started for 1-4 d when appropriate to stimulate gastrointestinal functioning and promote endocrine and metabolic maturity (50)(51)(52) (8,50,53). Most preterm infants cannot meet these high needs through enteral intake of breast milk or standard formula alone (53)(54)(55).…”
Section: $Dmentioning
confidence: 99%
“…21 HM is started for 1-4 d when appropriate to stimulate gastrointestinal functioning and promote endocrine and metabolic maturity (50)(51)(52) (8,50,53). Most preterm infants cannot meet these high needs through enteral intake of breast milk or standard formula alone (53)(54)(55).…”
Section: $Dmentioning
confidence: 99%
“…68 Because of the lack of harm and the likely physiological benefits mentioned previously, it is routine practice to commence enteral feeds in very low birth weight infants as early as possible, preferably with maternal breast milk. Once trophic feeds have been started, the timing of increasing enteral feeds is still unclear.…”
mentioning
confidence: 99%
“…However, the minimal feeding group also had prolonged parenteral nutrition and central line placement, which carries other risks unrelated to NEC. In a 2013 Cochrane review, Morgan et al determined that there is insufficient evidence showing that early trophic feedings compared to enteral fasting or delayed enteral feeding improves feeding tolerance or prevents NEC (24). Other studies have demonstrated similar findings.…”
Section: Enteral Feeding Techniquesmentioning
confidence: 99%